Effectiveness of Self-Instructional Module on Knowledge and Attitude Regarding Hepatitis B Infection of Schoolchildren among Primary School Teachers in Selected Schools at Holenarasipura, Karnataka - G. Madhusudhana, K. (International Journal of Nursing Research, 2023)
Aim: The aim of this study was to assess the effectiveness of self-instructional module on knowledge and attitude regarding hepatitis B infection among primary school teachers. Background: Hepatitis B is a viral disease caused by hepatitis B virus which leads to inflammation of liver, cirrhosis, and cancer of liver if the disease is progress the infected person will die. It is mainly transmitted through blood contact, in school environment, there is chance to spread from infected child to healthy child during contact with body fluid. More than 2 billion people worldwide have evidence of past current HBV infection. India has estimated endemicity of hepatitis B every year over 1,00,000 Indians die due to illness related to HBV. This study attempts to evaluate the effectiveness of self-instructional module on knowledge and attitude regarding hepatitis B infection of schoolchildren among primary schoolteachers in selected schools at Holenarasipura. Methods: The study involved pre-experimental one group pre-test post-test design. Non-randomized convenient technique was used. Data were collected from 60 samples. Results: The study shows that knowledge score of school teachers in pre-test was 44%, in post test 78.5%. And pre-test attitude score 47.1%, post test attitude 78.8%. Hence, they gained 34.5% of more knowledge and 31.7% of attitude after the administration of self-instructional module. There was a moderately positive correlation between knowledge and attitude among the primary school teachers. (r + 0.657 in pre-test and +0.497.